Sueño Bay adventures. 5, Crystal Cave - Deas, Mike, 1982-; Deas, Nancy (Orca Book Publishers, 2024)
"When Ollie's grandpa becomes ill and Ollie faces the possibility of having to leave his home in Sueño Bay, he and his friends set off on a race against time to find the legendary mother crystal known for its incredible healing powers. What they don't know is that a secret group of crystal keepers have dedicated themselves to guarding the cave that holds the mother crystal. If Ollie doesn't take the crystal, he won't be able to cure his grandpa. But if he does, the power of the crystal could shift the balance of the island and destroy Sueño Bay."--Amazon.